2012
DOI: 10.1523/jneurosci.1572-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Withdrawal Enhances Constitutive μ-Opioid Receptor Activity in the Ventral Tegmental Area

Abstract: -Opioid receptors (MORs) in the ventral tegmental area (VTA) are pivotally involved in addictive behavior. While MORs are typically activated by opioids, they can also become constitutively active in the absence of any agonist. In the current study, we present evidence that MOR constitutive activity is highly relevant in the mouse VTA, as it regulates GABAergic input to dopamine neurons. Specifically, suppression of MOR constitutive activity with the inverse agonist KC-2-009 enhanced GABAergic neurotransmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 72 publications
3
34
0
Order By: Relevance
“…Cessation of opiates leads to cellular and behavioral symptoms of withdrawal (1216). An intriguing hypothesis of drug addiction suggests that chronic opiates increase MOR constitutive activity (MOR CA ) to preserve physical and psychological dependence (1721), which is enhanced by enkephalins (22). Whether MORs adopt constitutive signaling states in other disease syndromes, such as chronic pain, is unknown.…”
mentioning
confidence: 99%
“…Cessation of opiates leads to cellular and behavioral symptoms of withdrawal (1216). An intriguing hypothesis of drug addiction suggests that chronic opiates increase MOR constitutive activity (MOR CA ) to preserve physical and psychological dependence (1721), which is enhanced by enkephalins (22). Whether MORs adopt constitutive signaling states in other disease syndromes, such as chronic pain, is unknown.…”
mentioning
confidence: 99%
“…As neutral antagonists for KORs are not well characterized, we tested the effect of CTOP (a neutral mu-opioid antagonist; Hawkins et al . 1989;Meye et al . 2012) on basal signaling.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing hypothesis of drug addiction suggests that chronic opiates increase MOR constitutive activity to preserve physical and psychological dependence (Wang et al, 1994, Liu and Prather, 2001, Wang et al, 2004, Shoblock and Maidment, 2006, Meye et al, 2012), which is enhanced by the action of endogenously released enkephalins in the brain (Shoblock and Maidment, 2007). Similarly, prolonged administration of exogenous opioid agonists, such as morphine or DAMGO, have been shown to cause an increase in the number of constitutively active opioid receptors during the period of opioid dependence (Wang et al, 2001a, Sadee et al, 2005, Walker and Sterious, 2005, Xu et al, 2007, Sally et al, 2010).…”
Section: Mu Opioid Receptor Constitutive Activity (Morca) Inhibits Lsmentioning
confidence: 99%
“…Constitutive activity is experimentally observable as increased basal GTPγS 35 binding, increased B max of the agonist-responsive high-affinity GTPγS 35 binding site and suppressed forskolin-stimulated cAMP accumulation. While constitutive activity is usually difficult to detect outside of in vitro heterologous cell expression systems, as described above (Costa and Herz, 1989, Liu and Prather, 2001, Wang et al, 2007), MOR CA has been observed in tissue obtained from the striatum (Wang et al, 2004, Shoblock and Maidment, 2006) and the ventral tegmental area (Meye et al, 2012) of morphine-dependent mice. Inverse agonists decreased basal GTPγS 35 binding, produced cAMP superactivation and disinhibited GABAergic signaling, indicative of acquired state-dependent activity following chronic receptor stimulation.…”
Section: Mu Opioid Receptor Constitutive Activity (Morca) Inhibits Lsmentioning
confidence: 99%